Analisis Numerik Perpindahan Panas Pada Saluran Pendingin Plastik Injeksi Molding Menggunakan Polyhedral Mesh: Analisis Numerik Perpindahan Panas Pada Saluran Pendingin Plastik Injeksi Molding Menggunakan Polyhedral Mesh - angger bagus prasetiyo (Politeknik Manufaktur Negeri Bangka Belitung, 2019)
The use of mesh types and mesh manufacturing density in a simulation play a very important role, this is because it minimizes computational time and cost and gets the desired analysis results. In this study, presents the CFD analysis of heat transfer that occurs in plastic injection mold cooling channels using polyhedral mesh. The most important part of the simulation is the select mesh types. Mesh is good, affects the calculation results of a simulation. The use of this type of mesh itself also affects the temperature field and the temperature profile that occurs in the cooling channel as well as the contour profile resolution. The use of polyhedral mesh for complex geometric shapes such as injection molds on plastic product cooling channels is able to reduce the iteration time of the simulation and can speed up the convergence of calculations, this is evidenced by the results of iteration simulation on the straight channel capable of converging at the 268th iteration of a total of about 1000 iterations and iterations of convergent conformal channel simulations on the 232nd iteration with a total of about 1000 iterations.